Tyler Perry's I can do bad all by myself [videorecording (DVD)] - Perry, Tyler; Perry, Tyler; Henson, Taraji P.; Rodriguez, Adam, 1975-; Knight, Gladys, 1944-; Blige, Mary J.; Perry, Tyler (Lionsgate, 2010)
After Madea catches sixteen-year-old Jennifer and her two younger brothers looting her home, she decides to take matters into her own hands and delivers the young delinquents to the only relative they have: their aunt April. A heavy-drinking nightclub singer who lives off of her married boyfriend, April wants nothing to do with them. But her attitude begins to change when Sandino, a handsome Mexican immigrant looking for work, moves into April's basement room. Making amends for his own past, Sandino challenges April to open her heart. Now, April has to decide between her old ways and the new possibilities of family, faith, and love.